Associations Between Factors Across Life and One-Legged Balance Performance in Mid and Later Life: Evidence From a British Birth Cohort Study - Blodgett, Joanna M.; Cooper, Rachel; Davis, Daniel H. J.; Kuh, Diana; Hardy, Rebecca (Frontiers in Sports and Active Living, 2020)
Introduction: Despite its associations with falls, disability and mortality, balance is an under-recognised and frequently overlooked aspect of physical ageing. Evidence exploring associations between factors across life and balance is limited. Understanding what contributes to balance ability can help identify protective factors and appropriate interventions across the life course. This study aimed to: i) identify socioeconomic, anthropometric, behavioural, health and cognitive factors that are associated with balance; ii) explore how these associations change with age. Methods: Data came from 3111 members of the MRC National Survey of Health and Development, a British birth cohort study. Multilevel models examined how one-legged standing balance (assessed at ages 53, 60-64 and 69) was associated with fifteen factors across life: sex, maternal education (4y), paternal occupation (4y), own education (26y), own occupation (53y) and contemporaneous measures (53, 60-64, 69y) of height, BMI, physical activity, smoking, diabetes, respiratory symptoms, cardiovascular events, knee pain, depression and verbal memory. Age and sex interactions with each variable were assessed. Results: Men had 18.8% (95%CI: 13.6, 23.9) longer balance times than women at age 53, although this difference decreased with age (11.8% at age 60-64 and 7.6% at age 69). Disadvantaged socioeconomic position in childhood and adulthood, low educational attainment, unhealthy behaviours, poor health status, lower cognition, higher BMI and shorter height were associated with poorer balance at all three ages. For example, at age 53, those from the lowest paternal occupational classes had 29.6% (22.2, 38.8%) worse balance than those from the highest classes. Associations of balance with socioeconomic indicators, cognition and physical activity became smaller with age, while associations with knee pain and depression became larger. There were no sex differences. In a combined model, the majority of factors remained associated with balance. Discussion: This study identified numerous risk factors across life that influence balance ability and highlighted diverse patterns of association with age, suggesting that there are opportunities to intervene in early, mid and later life. A multifactorial approach to intervention, at both societal and individual levels, may have more benefit than focus on one single risk factor.